Bridging the Gap: A Systematic Review of Deep Learning Pedagogy for Indonesia’s Curriculum Reform - Siti Nurhasanah; Dina Sutiana; Fitrian Nabil; Ikang Fauji; Sopyan Hendriyan; Dian Dian (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to systematically analyse the implementation of deep learning pedagogies across international educational contexts and assess their relevance to Indonesia's curriculum reform. Deep learning is defined as student-centred instruction that enhances critical thinking, knowledge transfer, and reflective understanding. A systematic literature review (SLR) was conducted following the PRISMA 2020 guidelines, synthesising 31 peer-reviewed articles published between 2015 and early 2024. The findings indicate that project-based, inquiry-based, and reflective learning strategies are most commonly employed to foster deep cognitive engagement. However, successful adoption requires comprehensive policy support, continuous teacher professional development, and adaptation to local cultural and infrastructural contexts. In Indonesia, although the Kurikulum Merdeka reflects the principles of deep learning, its implementation remains fragmented and uneven. The study concludes that embedding deep learning in the Indonesian curriculum necessitates systemic reforms in curriculum design, assessment practices, teacher preparation, and digital infrastructure. These insights offer practical implications for policymakers and educators aiming to align global pedagogical innovations with national educational goals.